ABO-Incompatible Living Donor Liver Transplantation from Hepatitis B Core Antibody Positive Donor to Hepatitis C Liver Cirrhosis Recipient: A Case Report. (15th June 2014) - Umemura, Akira; Nitta, Hiroyuki; Sasaki, Akira; Takahara, Takeshi; Hasegawa, Yasushi; Wakabayashi, Go
Abstract : Herein, we describe an extremely rare experience of a patient with liver cirrhosis from hepatitis C virus (LC-HCV) who underwent an ABO-incompatible living donor liver transplantation (ABO-I-LDLT) using a hepatitis B core antibody (HBc-Ab) positive donor's liver graft. A 47-year-old Japanese woman with end stage LC-HCV, as a recipient, was preoperatively administered rituximab, mycophenolate mofetil, and steroids without plasma exchange. A routine ABO-I-LDLT procedure was applied using her daughter's HBc-Ab positive liver graft. Prophylaxis of the hepatitis B virus (HBV) infection using hepatitis B immunoglobulin (HBIG) and entecavir had been properly administered. Three months after the ABO-I-LDLT, HCV hepatitis relapsed. To date, this patient has been under antiviral therapy and prophylaxis of HBV infection using HBIG, while entecavir has been continued. The cognitions and techniques with regard to ABO-I-LDLT, prophylaxis of HBV cross infection, various patterns of immunosuppression, and antiviral therapy for HCV relapse are indispensable in managing a transplant recipient. According to the prophylaxis of HBV cross infection under ABO-I-LDLT, it may be very important to keep the HBs-Ab titer higher than usual for HBV naïve recipients, because severe systemic immunosuppression can cause de novo hepatitis.